Kajian Makna Kata Simbolik “Mulak Ari” dalam Marhata-Hata pada Adat Tradisi Pernikahan Batak Mandailing - Eka Indriyani; Rosmawaty Harahap; Elly Prihasti Wuriyani (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2022)
Tradition is one of the habits passed down from generation to generation by a group of people based on developing cultural values. The number of traditions that develop in each region is a culture that has been successfully preserved so that future generations will still know how the traditions and culture of certain tribes or ethnicities are. In this paper, the author aims to provide an understanding and description of the study of oral traditions owned by the Mandailing Tribe. The form of tradition discussed in this study is the Batak Mandailing Marhata-Hata Marriage Tradition: "Mulak Ari". The methodology used is descriptive qualitative approach and data analysis method using content analysis method. The conclusion of this research is that in the Mandailing Batak community, the Marhata-hata Marriage Customary tradition has until now been believed to have benefits and it is believed that if you carry out this tradition, it will bring blessings. Mulak Ari's oral literature in the wedding ceremony was spoken at Jorong Paroman Bondar. Marhata-hata is spoken by traditional leaders (hatobangon). Mulak Ari is the final part of a series of ceremonies held at the bride's house and attended by the bride and groom, the entire family who held the party, traditional leaders, and invitees.